2013
DOI: 10.1007/s00216-013-6753-0
|View full text |Cite
|
Sign up to set email alerts
|

Determination of sulfite with emphasis on biosensing methods: a review

Abstract: Sulfite is used as a preservative in a variety of food and pharmaceutical industries to inhibit enzymatic and nonenzymatic browning and in brewing industries as an antibacterial and antioxidizing agent. Convenient and reproducible analytical methods employing sulfite oxidase are an attractive alternative to conventional detection methods. Sulfite biosensors are based on measurement of either O2 or electrons generated from splitting of H2O2 or heat released during oxidation of sulfite by immobilized sulfite oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(49 citation statements)
references
References 59 publications
0
48
0
1
Order By: Relevance
“…The available methods for the detection of sulphites in foods have been extensively reviewed (Isaac et al, 2006;Ruiz-Capillas and Jiménez-Colmenero, 2009;Pundir and Rawal, 2013). There are several Official AOAC methods for the detection of sulphites in meats (qualitative), fruits and wines (http://www.eoma.aoac.org/).…”
Section: Methods Of Detection Of Sulphites In Foodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The available methods for the detection of sulphites in foods have been extensively reviewed (Isaac et al, 2006;Ruiz-Capillas and Jiménez-Colmenero, 2009;Pundir and Rawal, 2013). There are several Official AOAC methods for the detection of sulphites in meats (qualitative), fruits and wines (http://www.eoma.aoac.org/).…”
Section: Methods Of Detection Of Sulphites In Foodsmentioning
confidence: 99%
“…Tartaric acid allows the selective extraction of free sulphites, whereas an alkaline extractant containing potassium sodium tartrate allows detecting total sulphites. The LOD is 0.5 mg/kg (Pundir and Rawal, 2013).…”
Section: Ion Chromatographymentioning
confidence: 97%
“…The reducing equivalents are transferred via intramolecular electron transfer (IET) to the cytb5 domain of SOx and from there to cytc as the physiological electron acceptor. Cytc can be replaced by an electrode, either by using mediators or via direct electron transfer (DET), and SOx can hence be used to make both second and third generations enzymatic sensors (Pundir and Rawal, 2013;Spricigo et al, 2010). DET between SOx and different electrodes have been reported (Elliott et al, 2002;Ferapontova et al, 2003;Frasca et al, 2012;Sezer et al, 2010), where efficient ET can be achieved by employing cationic surface modifiers to promote adsorption of SOx in a suitable orientation.…”
Section: Introductionmentioning
confidence: 99%
“…From the above results in Table ( 4), it was concluded that, large amounts of synthetic food flavourants may be bound with unSFA and TS to give a new complex secreted in feces when compared with control feces. Generally, this trend was observed in total lipids which secreted in and lipid fractions which secreted in feces via bound with synthetic flavourants (Chen and Ni 2009;Ohtsuki et al, 2012;Pundir and Rawal 2013).…”
Section: Synthetic Food Flavourantsmentioning
confidence: 82%